2013
DOI: 10.1177/0170840613483655
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Control Systems and Pay-for-Performance in the Public Service

Abstract: Under certain conditions, output related performance measurement and pay-for-performance produce negative outcomes. We argue that in public service, these negative effects are stronger than in the private sector. We combine Behavioural Economics and Management Control Theory to determine under which conditions this is the case. We suggest as alternatives to the dominant output related pay-for-performance systems selection and socialization, exploratory use of output performance measures, and awards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
224
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(247 citation statements)
references
References 201 publications
(248 reference statements)
7
224
0
6
Order By: Relevance
“…Further, the means to reach preferable outcomes are oft en not known or highly dependent on context (e.g. Van Th iel and Leeuw 2002;Ordóñez et al 2009;Maynard 2012;Frey et al 2013). Th ese divergent conceptions among elected representatives are usually also present among employees; for example managers, technicians, street-level bureaucrats.…”
Section: Measures Are Taken In Order To Rectify Deviant Results and Imentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the means to reach preferable outcomes are oft en not known or highly dependent on context (e.g. Van Th iel and Leeuw 2002;Ordóñez et al 2009;Maynard 2012;Frey et al 2013). Th ese divergent conceptions among elected representatives are usually also present among employees; for example managers, technicians, street-level bureaucrats.…”
Section: Measures Are Taken In Order To Rectify Deviant Results and Imentioning
confidence: 99%
“…As a result, PIs might turn out to be too narrow, as only that which can be agreed on is covered by the indicators (Van Th iel and Leeuw 2002; Ordóñez et al 2009), or too wide, when diff erent interpretations are encompassed in order to reach a consensus or manage uncertainty about causal conjunctions (Pollitt et al 2010). Too few indicators have the tendency to foster goal displacement through knowledge about how judgments are made (Pidd 2005;Frey et al 2013), while too many indicators tend to be too challenging and therefore tend to make the model ineffi cient and undermine ambitions (de Bruijn 2002;Frey et al 2013). …”
Section: Measures Are Taken In Order To Rectify Deviant Results and Imentioning
confidence: 99%
See 1 more Smart Citation
“…Current organisational reforms in the public sector clearly give priority to extrinsic HRM practices and tools such as, for instance, pay-for-performance, results-oriented appraisal, and development of competition between employees. These kinds of HRM practices, which are well developed in the private sector, are probably not adapted to public organisations or to their employees (Frey et al, 2013). HRM specialists have demonstrated that contemporaneous organisations make use of HR tools and practices more according to ideological arguments than to empirical evidence (Pfeffer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is an intense discussion about what motivates public sector employees and a number of studies support the notion that public employees are motivated less by monetary rewards than their private counterparts (Frey et al, 2013). One of the instruments is recognition by organization and manager.…”
Section: Reward System and Recognitionmentioning
confidence: 99%